Erlotinib Resistance in Lung Cancer: Current Progress and Future Perspectives - Tang, Joy; Salama, Rasha; Gadgeel, Shirish M.; Sarkar, Fazlul H.; Ahmad, Aamir (Frontiers in Pharmacology, 2013)
Lung cancer is the most common cancer in the world. Despite modern advancements in surgeries, chemotherapies and radiotherapies over the past few years, lung cancer still remains a very difficult disease to treat. This has left the death rate from lung cancer victims largely unchanged throughout the past few decades. A key cause for the high mortality rate is the drug resistance that builds up for patients being currently treated with the chemotherapeutic agents. Although certain chemotherapeutic agents may initially effectively treat lung cancer patients, there is a high probability that there will be a reoccurrence of the cancer after the patient develops resistance to the drug. Erlotinib, the epidermal growth factor receptor (EGFR)-targeting tyrosine kinase inhibitor, has been approved for localized as well as metastatic non-small cell lung cancer where it seems to be more effective in patients with EGFR mutations. Resistance to erlotinib is a common observation in clinics and this review details our current knowledge on the subject. We discuss the causes of such resistance as well as innovative research to overcome it. Evidently, new chemotherapy strategies are desperately needed in order to better treat lung cancer patients. Current research is investigating alternative treatment plans to enhance the chemotherapy that is already offered. Better insight into the molecular mechanisms behind combination therapy pathways and even single molecular pathways may help improve the efficacy of the current treatment options.